ANALYSIS OF LAW NUMBER 56 PRP 1960 ON THE PLEDGING OF ANCESTRAL LAND IN NAGARI KOTO GADANG SOLOK REGENCY: ANALISIS UNDANG-UNDANG NOMOR 56 PRP 1960 TERHADAP PAGANG GADAI TANAH PUSAKO KAUM DI NAGARI KOTO GADANG KABUPATEN SOLOK - Surya, Febri Yuranda (Asosiasi Dosen Hukum Acara Perdata (ADHAPER), 2025)
Article 7 of Law No. 56 PRP of 1960 regulates the term of agricultural land mortgages, which is 7 years. After this period, the mortgage holder is obliged to return the land to its owner without paying a ransom. However, in practice, the Minangkabau indigenous community still widely practices land mortgages with varying terms and conditions. Court decisions in cases of disputes over communal land mortgages also implement different provisions. Some implement the provisions of Article 7 of Law No. 56 PRP of 1960, while others apply the provisions of Minangkabau customary law. This can be evidenced by the issuance of Supreme Court Decision Number: 1540K/Pdt/2005 dated June 19, 2006, which accommodates the provisions of Article 7 of Law No. 56/Prp/1960 concerning agricultural land mortgages without redemption money, and the Solok District Court Decision on case number: 05/Pdt.G/2003/PN.SLK dated April 20, 2004, which decided the case based on Article 7 of Law No. 56 Prp of 1960. The practice of pawnbroking that is not in accordance with Law No. 56 Prp of 1960 Article 7 has caused confusion among the people of West Sumatra. This has resulted in the people of Nagari Koto Gadang, Gunung Talang District, having different views on Law No. 56 Prp 1960 Article 7 on the Implementation of Pawnbroking. The research method used in this study is empirical juridical.